New Right 2.0: Teacher populism on social media in England. (24th July 2020) - Watson, Steven
Abstract : This article is concerned with teacher populism on social media in England. This has grown in the last 10 years, facilitated by Twitter. While it appears to be a response to challenging working conditions and declining pay, it has largely been driven by conservative political strategy, an adaptation of the New Right coalition between social conservatives and economic liberals of the 1970s. New Right 2 . 0, as I frame it here, is a New Right project for the social media age, but also goes deeper into society to promote civic capitalism—so‐called 'Big Society'. New Right 2.0, like its predecessor, is an attempt to create an aggregated passive acceptance of free‐market ideology by creating division and indifference, setting one group against another, using the state to reward its proponents and to discipline its objectors. Teacher populism, though modest in numbers and specific to a particular public service, uses the language of populism to promote its cause, wanting to give voice to the ordinary teacher against a liberal educational elite which includes academics, local education authorities and teaching unions. This article contributes to an understanding of the social, cultural and political processes that are at play as part of a populist rupture.